Led radiation with different spectra influence on plants development at different stages of vegetation; Ресурсоэффективным технологиям - энергию и энтузиазм молодых - Starodubtseva D. V. Daria Vyacheslavovna; Turanov S. B. Sergey Borisovich; Yakovlev A. N. Aleksey Nikolaevich; Kozyreva I. N. Irina Nikolaevna (Modern issues of science and technologies, 2014)
Заглавие с титульного экрана